2022
DOI: 10.1007/s10534-022-00466-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional insights into iron acquisition from lactoferrin and transferrin in Gram-negative bacterial pathogens

Abstract: Iron is an essential element for various lifeforms but is largely insoluble due to the oxygenation of Earth’s atmosphere and oceans during the Proterozoic era. Metazoans evolved iron transport glycoproteins, like transferrin (Tf) and lactoferrin (Lf), to keep iron in a non-toxic, usable form, while maintaining a low free iron concentration in the body that is unable to sustain bacterial growth. To survive on the mucosal surfaces of the human respiratory tract where it exclusively resides, the Gram-negative bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Likewise three terms initially lacking functional information, were respectively found to correspond to the periplasmic iron-binding shuttle, FbpA (K02012), the non-heme ferritin iron storage protein, FtnA (K02217), and the acid-inducible, cytoplasmic membrane-bound iron transporter, EfeU (K07243). Iron acquisition is directly linked to colonisation and virulence in many important human pathogens [43]; therefore, the differences in iron requirements between BV-associated taxa and health-associated lactobacilli may present a therapeutic opportunity [44].…”
Section: Resistance Mechanisms Against Host Cationic Antimicrobial Pe...mentioning
confidence: 99%
“…Likewise three terms initially lacking functional information, were respectively found to correspond to the periplasmic iron-binding shuttle, FbpA (K02012), the non-heme ferritin iron storage protein, FtnA (K02217), and the acid-inducible, cytoplasmic membrane-bound iron transporter, EfeU (K07243). Iron acquisition is directly linked to colonisation and virulence in many important human pathogens [43]; therefore, the differences in iron requirements between BV-associated taxa and health-associated lactobacilli may present a therapeutic opportunity [44].…”
Section: Resistance Mechanisms Against Host Cationic Antimicrobial Pe...mentioning
confidence: 99%
“…There is a contrasting regulation of Tsf levels in humans and mice upon infection. Downregulation of Tsf at the site of infection in humans may be due to iron being relocated by serum Tsf to other tissues because many bacterial species can utilize human Tsf for iron acquisition ( 11 , 42 ). In mice, the disparity in Tsf regulation could be attributed to the distinct pathogen-host interactions and also due to differences in murine protein ( 43 ).…”
Section: Host Iron Regulation During Pathogen Attackmentioning
confidence: 99%
“…In addition, some infectious bacterial species have specific membrane receptors, capable of directly binding Tsf and LF which are the key players of nutritional immunity. After binding, iron ions are extracted from Tsf and LF by these special membrane proteins, shifted to periplasm, and then bounded by ferric binding proteins and transported to the cytoplasm where they are utilized by the bacterial cells ( 42 , 184 ). By employing these strategies, pathogens successfully acquire iron from different sites within the host, ensuring their survival and enhancing their pathogenic potential.…”
Section: Bacterial Iron Acquisition Against Host Barriersmentioning
confidence: 99%
“…Also, it was reported that an FcLf adduct, created from hLf that was fused with an Fc domain of IgG, strongly induced expression of PI3K, with subsequent activation of the AKT/mTOR signaling pathway (Zaczyńska et al 2022 ). In addition, Lf not only provides ferric iron for mammals, but it can also be used as a donor by some pathogenic bacteria (Chan et al 2022 ). These workers revealed molecular level details about the mechanism of iron transport in Moraxella catarrhalis by analyzing the crystal structures of the M. catarrhalis FbpA in the holo- and apo-conformations.…”
mentioning
confidence: 99%